Patofisiologi, Pemantauan Dan Pengelolaan Penderita Trauma Kepala - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT In the context of Cephalic trauma, there is a need to learn more about its phatophisiology, monitoring and its management . Teoritically, there we know that the view on this science will become very important in doing an intensive care, especially where are an emergency case already done. Actually, the aim of management in the intensive therapy unit is to take care the availability and its adequancy of blood sirculation and perfussion pressure in brain. Therefore, using this view, then we learn about how important the fucntion of monitoring and management of intensive care.